2022
DOI: 10.1002/ps.6927
|View full text |Cite
|
Sign up to set email alerts
|

Dissipative behavior, residual pattern, and risk assessment of four pesticides and their metabolites during tea cultivation, processing and infusion

Abstract: Background: In recent years, metabolic products of pesticides have gained much attention due to their substantial characteristics as organic pollutants. So far, the behavior and metabolite levels of pesticide metabolites in crops have not been characterized well. In the present study, four registered pesticides (imidacloprid, diafenthiuron, malathion and chlorothalonil) were applied on tea plants in Fujian and Sichuan to characterize their metabolites residue pattern and dietary risk.Results: Four pesticides d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 45 publications
(80 reference statements)
0
12
0
Order By: Relevance
“…However, the metabolites of imidacloprid (desnitro-imidacloprid, desnitro-olefin-imidacloprid) were detected in this study instead of the parent pesticide. Some researches have shown that several metabolites of neonicotinoids are as toxic as the parent pesticides . Triazole fungicides, toxic to a wide range of nonspecific organisms, easily accumulate in soil due to their hydrophobicity and low molecular weight and therefore may change physicochemical properties and affect the balance of the ecological system .…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…However, the metabolites of imidacloprid (desnitro-imidacloprid, desnitro-olefin-imidacloprid) were detected in this study instead of the parent pesticide. Some researches have shown that several metabolites of neonicotinoids are as toxic as the parent pesticides . Triazole fungicides, toxic to a wide range of nonspecific organisms, easily accumulate in soil due to their hydrophobicity and low molecular weight and therefore may change physicochemical properties and affect the balance of the ecological system .…”
Section: Resultsmentioning
confidence: 99%
“…These metabolites accumulate in the lung and liver, thereby threatening human health . Wu et al indicated that the chronic hazard quotient of diafenthiuron and its metabolites was high and caused an unacceptable health risk to tea consumers due to the high residue and low ADI, even though there was a lower transfer rate in tea infusion. In addition, these metabolites could be detected after 21 days, revealing that they were persistent in tea plants .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations